2016
DOI: 10.1111/phn.12276
|View full text |Cite
|
Sign up to set email alerts
|

Adapting Animal‐Assisted Therapy Trials to Prison‐Based Animal Programs

Abstract: Prison-based animal programs have shown promise when it comes to increased sociability, responsibility, and levels of patience for inmates who participate in these programs. Yet there remains a dearth of scientific research that demonstrates the impact of prison-based animal programs on inmates' physical and mental health. Trials of animal-assisted therapy interventions, a form of human-animal interaction therapy most often used with populations affected by depression/anxiety, mental illness, and trauma, may p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 20 publications
1
13
0
Order By: Relevance
“…In particular, animals appear to be increasingly incorporated into correctional programs in prison as part of vocational and social skills training [ 20 ] and in the treatment of substance dependence [ 21 , 22 ]. Several studies have reported positive psychological and physiological effects of prison-based animal programs and animal assisted interventions with inmates, which confirm the general idea that human–animal interactions contribute to human health and well-being [ 23 , 24 , 25 , 26 , 27 , 28 ]. However, even if they have shown promising results, only Japerson (2010) and Burger (2011) went through health outcomes of animal assisted therapy with drug addicted inmates [ 29 , 30 ].…”
Section: Introductionsupporting
confidence: 54%
“…In particular, animals appear to be increasingly incorporated into correctional programs in prison as part of vocational and social skills training [ 20 ] and in the treatment of substance dependence [ 21 , 22 ]. Several studies have reported positive psychological and physiological effects of prison-based animal programs and animal assisted interventions with inmates, which confirm the general idea that human–animal interactions contribute to human health and well-being [ 23 , 24 , 25 , 26 , 27 , 28 ]. However, even if they have shown promising results, only Japerson (2010) and Burger (2011) went through health outcomes of animal assisted therapy with drug addicted inmates [ 29 , 30 ].…”
Section: Introductionsupporting
confidence: 54%
“…However, participants were not randomly allocated to the program, and those who choose to participate in DTPs may differ from those who do not engage with such programs [ 9 , 11 ]. It was not feasible to conduct comparable qualitative evaluations for an appropriate control group; this is a key limitation of qualitative DTP evaluations which will need to be addressed despite the challenges of conducting research in a custodial context [ 7 , 11 , 24 , 47 ]. Nonetheless, the program appeared to be effective in engaging those with low levels of prior engagement with education or training opportunities, for example, as indicated by participant characteristics and program records.…”
Section: Discussionmentioning
confidence: 99%
“…Offenders have multiple needs and interventions tackling a range of problems are considered the most effective [ 32 , 33 ]. A range of positive outcomes across several domains have been identified for DTPs, using both qualitative and quantitative methods of evaluation [ 7 , 9 , 11 ], which suggests that DTPs may be particularly effective in addressing the multiple needs of offenders [ 34 , 35 , 47 ]. However, the evaluation of prison animal programs is challenging because of the constraints imposed by an applied context, in which multiple individual and program variables potentially confound results [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…A substantial body of work on the human‐dog relationship has developed since the 1980s, chiefly in the health field, leading to findings that dogs can improve physical health (e.g., myocardial infarction, asthma), mental health (e.g., anxiety, depression) and social integration (Alison & Ramaswamy, ; Friedmann, Katcher, Lynch, & Thomas, ; McNicholas et al, ; Morrison, ; Ownby, Johnson, & Peterson, ). Unfortunately, when these studies were replicated many of these findings appeared contradictory and inconclusive (McNicholas et al, ).…”
Section: Introductionmentioning
confidence: 99%